Out‐of‐Hospital Cardiac Arrest: Does a History of Myocarditis/Perimyocarditis Affect the Outcome? A Swedish Nationwide Study - Sadek Nadhir; Marie Björkenstam; Emanuele Bobbio; Berkan Eken; Charlotta Ljungman; Christian Polte; Araz Rawshani; Entela Bollano (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Acute myocarditis/perimyocarditis presents with a variable prognosis ranging from complete recovery to end‐stage heart failure (HF), sudden cardiac arrest, and death. The relationship between a prior history of myocarditis/perimyocarditis and outcomes in out‐of‐hospital cardiac arrest remains unclear. Methods and Results Using the SCRR (Swedish Cardiopulmonary Resuscitation Registry), we analyzed 54 568 cases of out‐of‐hospital cardiac arrest from 2010 to 2020 where cardiopulmonary resuscitation was attempted. Patients with a history of myocarditis/perimyocarditis were compared with those without in terms of characteristics and survival. Four hundred ninety‐eight patients (0.9%) had a history of myocarditis/perimyocarditis. These patients were predominantly men (73.8%), had an average age of 68 years, displayed a higher prevalence of cardiovascular comorbidities, and more frequently displayed shockable initial rhythms (28.7% versus 23.1%). Prior myocarditis/pericarditis did not correlate with worse short‐term (odds ratio [OR], 0.91 [95% CI, 0.61–1.33]) or long‐term survival (hazard ratio [HR], 1.01 [95% CI, 0.91–1.13]). Patients with myocarditis/perimyocarditis with concomitant HF showed worse long‐term survival in unadjusted analyses. Adjusted analyses confirmed that absence of HF was linked to improved short‐term survival (OR, 1.46 [95% CI, 1.32–1.62]), whereas prevalence of HF was a predictor for worsened long‐term survival (HR, 0.91 [95% CI, 0.91–0.95]) after out‐of‐hospital cardiac arrest. Analyses were adjusted for myocarditis/perimyocarditis, sex, age, HF, time to cardiopulmonary resuscitation start, and initial rhythm. Conclusions Prior myocarditis/perimyocarditis per se did not contribute to a worsened outcome following out‐of‐hospital cardiac arrest. However, the presence of concomitant HF was linked to unfavorable short‐ and long‐term outcomes.